Ziemia niczyja. Zwroty badawcze w literaturoznawstwie i ich konsekwencje dla nauczania literatury - Koziołek, Krystyna (Postscriptum Polonistyczne, 2020)
The author of the article poses a question concerning adequacy of research proposals inspired by the circle called ‘the ethic of reading’ and ‘theological return’. She points out to the fact that questions concerning axiology of reading, that have been recently considered oldfashioned, are the classical problems of humanistics today. It results from the notion of interference between different disciplines, but above all from the fact that ethical response to the work of literature is an integral element of individual reading. Ethics appears in readers mind before poetics. It makes possible uniting a reader (that has been wrongly divided into an emotional and a suspicious kind) into one subject of multiple reading experience. Powerful institutions of a text are based after all on individual reading of a subject that experiences, understands and evaluates the text.